Capabilities and competencies related to leadership performance effectiveness in the context of change in Malaysian Higher Education Institutions / Majid Ghasemy - Majid , Ghasemy (2017)
This study aimed at identifying the essential capabilities and competencies of leaders for effective university leadership, determining the extent to which these qualities explain leadership performance, and identifying the main priorities, values, challenges, as well as solutions from the viewpoints of Malaysian academic leaders. It is noteworthy that academic leaders refer to vice-chancellors, deputy vice-chancellors, deans, directors, deputy deans, deputy directors, heads of departments, as well as professors without formal positions in universities’ organizational charts. To collect data in the piloting phase, permission was obtained to utilize the scales which had been developed in Australian academic context to operationalize capabilities, competencies, and leadership performance. In addition, a new change-oriented capability scale was developed on the grounds of an extensive literature review focusing on change-oriented leadership. The theoretical validity of the scales was established and the scales were administered through one online platform. A number of 90 academic leaders from five public and four private universities completed the survey. Next, the reliability of the scales was estimated and the highly prominent elements in capabilities, competencies, and leadership performance in Malaysian Higher Education Institutions (HEIs) were descriptively highlighted. Also, Principal Component Analysis (PCA) and Velicer’s Minimum Average Partial (MAP) test were run to identify the main constructs under each domain of capabilities, competencies, and leadership performance. The resulting scales through these procedures as well as four open-ended questions related to Malaysian HE issues were used to collect data for the actual study. For this purpose, the online version of the survey was administered among academic leaders in 25 public and private universities. More than 400 surveys were collected, among which only 368 surveys were appropriate for data analysis. Next, IBM SPSS Statistics 23 was used for data screening and descriptive analysis whereas SmartPLS 3 was employed to develop a few models for the contribution of capabilities and competencies to leadership performance in Malaysian academic settings. The results of Partial Least Squares (PLS) algorithm were extended through running Finite Mixture Partial Least Squares (FIMIX-PLS) and Importance-Performance Map Analysis (IPMA) as well. Additionally, ATLAS.ti 7 was used to manage the collected qualitative data, and to analyze them, descriptive statistics and thematic analysis were undertaken. The results of the analysis highlighted the highly prominent items under each domain on the grounds of the actual study instrument. Additionally, five models for the contribution of capabilities and competencies to leadership performance in Malaysian HE and its sectors were developed. These models were underpinned by the qualitative data. Moreover, the examination of the qualitative data revealed five main areas of focus in Malaysian HE namely academic core activities, management, change & leadership, relationships, and work values. Even though the results of this study have several theoretical, practical, and methodological implications, upgrading the contents and processes of leadership developmental programs in each of Malaysian HE sectors deems to be considerably crucial.